2009
DOI: 10.1107/s1600536809053410
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin-lactum–chloranilic acid (1/1)

Abstract: In the title compound, C9H15NO·C6H2Cl2O4 [sytematic name: 2-aza­spiro­[4.5]decan-3-one–chloranilic acid (1/1)], the cyclo­hexane ring of the lactam molecule adopts a slightly distorted normal chair conformation and the five-membered 3-aza­spiro ring is in a slightly distorted chair conformation. The dihedral angle between the least-squares planes of the cyclohexane and 3-azaspiro rings is 84.0 (3)°. In the crystal, the chloranilic acid mol­ecule and the gabapentin-lactum mol­ecules are held together by strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…For spectroscopic studies of the interaction between triprolidine hydrochloride and serum albumins, see: Sandhya et al (2011). For related structures, see: Adam et al (2010); Dayananda et al (2011); Dutkiewicz et al (2010); Gotoh et al (2010); Hakim Al-arique et al (2010); Jasinski et al (2010); Parvez & Sabir (1997); Udachin et al (2011). For ring puckering parameters, see: Cremer & Pople (1975).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For spectroscopic studies of the interaction between triprolidine hydrochloride and serum albumins, see: Sandhya et al (2011). For related structures, see: Adam et al (2010); Dayananda et al (2011); Dutkiewicz et al (2010); Gotoh et al (2010); Hakim Al-arique et al (2010); Jasinski et al (2010); Parvez & Sabir (1997); Udachin et al (2011). For ring puckering parameters, see: Cremer & Pople (1975).…”
Section: Related Literaturementioning
confidence: 99%
“…The synthesis and spectroscopic studies of charge transfer complexes between chloranilic acid and some heterocyclic amines in ethanol (Al-Attas, Habeeb & Al-Raimi, 2009) have been studied. The crystal structures of triprolidine tetrachlorocuprate (II) (Parvez & Sabir, 1997), triethylammonium hydrogen chloranilate (Gotoh et al, 2010), chloranilic acid: a redetermination at 100 K (Dutkiewicz et al, 2010), bis(3-picoline) chloranilate chloranilic acid (Adam et al, 2010), Gabapentin-lactum-chloranilic acid (Jasinski et al, 2010) arique et al, 2010), bis(guanidinium) chloranilate (Udachin et al, 2011) and triprolinidium dipicrate (Dayananda et al, 2011) have been reported. In view of the importance of triprolidine, the paper reports the crystal structure of the title compound, (I).…”
Section: S1 Commentmentioning
confidence: 99%